2008
DOI: 10.1016/j.ahj.2008.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The Heart Failure Adherence and Retention Trial (HART): Design and rationale

Abstract: Background Heart failure (HF) is increasing in prevalence and associated with prolonged morbidity, repeat hospitalizations, and high costs. Drug therapies and lifestyle changes can reduce hospitalizations, but non-adherence is high, ranging from 30–80%. There is an urgent need to identify cost-effective ways to improve adherence and reduce hospitalizations. Trial Design HART evaluated the benefit of patient self-management (SM) skills training in combination with HF education, over HF education alone, on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…The value of articulating a hypothesized pathway, and collecting measurements for each of its links, lies in the ability to more precisely interpret the results of Phase III trials (Powell, Calvin, Mendes de Leon, Richardson, Grady, Flynn, Rucker-Whitaker, Janssen, et al, 2008). If the trial produces positive results, evidence specifically supporting each link of the chain strengthens the assertion that the observed effects were due to hypothesized pathways.…”
Section: The Orbit Model For Behavioral Treatment Developmentmentioning
confidence: 99%
“…The value of articulating a hypothesized pathway, and collecting measurements for each of its links, lies in the ability to more precisely interpret the results of Phase III trials (Powell, Calvin, Mendes de Leon, Richardson, Grady, Flynn, Rucker-Whitaker, Janssen, et al, 2008). If the trial produces positive results, evidence specifically supporting each link of the chain strengthens the assertion that the observed effects were due to hypothesized pathways.…”
Section: The Orbit Model For Behavioral Treatment Developmentmentioning
confidence: 99%
“…After title and abstract screening, 2312 were excluded using predefined criteria. Twenty full-text papers were retrieved for assessment, 13 of which were excluded on full text review (a review article [23]), four exercise training studies in a mixed HFPEF and systolic HF populations that failed report of outcomes in HFPEF subgroup [24][25][26][27], an exercise training study in HFPEF with no relevant reported outcomes [28], five exercise training studies in a non-HFPEF population [29][30][31][32][33], and two abstracts for an included HFPEF training study for which we subsequently identified a full paper [34,35]. Seven papers were therefore included reporting the results of five distinct studies.…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…Because double blinding in behavioral trials is generally not feasible, this was a single-blinded trial. 27 Subjects were assessed at baseline, month 3 and every 6 months after baseline for clinical events, blood pressure (BP), body mass index (BMI), and adherence. Lifestyle behaviors (diet, exercise, and substance use) and psychosocial distress factors were assessed annually.…”
Section: Methodsmentioning
confidence: 99%
“…27,49 The content was based on standard, published materials. 50,51 The instructors were professional health educators.…”
Section: Interventionsmentioning
confidence: 99%